Mauritius : Staff Report for the 2001 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2001)
Mauritius experienced a rebound in economic activity, following a severe drought. Executive Directors welcomed the tightening of monetary policy, and noted the reversal of the real currency appreciation. They supported the initiatives to strengthen and modernize the financial sector and the institutional framework for the conduct of monetary and exchange rate policy. They emphasized the need to reduce unemployment, and suggested that the quality and timeliness of economic and financial statistics are satisfactory from the standpoint of conducting surveillance.